Study of the diagnostic yield of cytology in pleural fluid in malignant pleural effusions in Tishreen University Hospital. (Latakia University Journal -Medical Sciences Series, 2024)
Background: Malignant pleural effusion (MPE) is a common global issue, resulting from direct invasion of the pleura by adjacent tumors or secondary to pleural metastases. Not all pleural effusions in patients with cancer are malignant, thus accurate diagnosis is crucial as it influences prognosis and treatment. Various methods are employed to diagnose effusions, with cytology being an initial investigation due to its relatively non-invasive nature. The diagnostic accuracy of cytology for MPE ranges between 40-87%.Objective: To evaluate the diagnostic value of cytology of pleural fluid in malignant pleural effusions at Tishreen University Hospital, and to classify the most common tumors causing malignant pleural effusion as diagnosed by cytology.Methods: The study included 85 patients: those with previously diagnosed tumors who developed pleural effusion for the first time, and patients who presented with pleural effusion for the first time with clinical or radiological suspicion of a tumor and were subsequently diagnosed. Pleural fluid samples were obtained via thoracentesis and sent for cytological examination. If the initial thoracentesis was negative, a second thoracentesis was performed in some patients.Results: The diagnostic value of cytology was 50.6%. The diagnostic yield was 40% on the first thoracentesis, and repeating the procedure improved the diagnostic value by 10.6%. The most frequently diagnosed  type was adenocarcinoma, accounting for 74.4%.Conclusion: Cytology is an important and useful initial investigation for diagnosing malignant pleural effusion. The diagnostic value improves with repeated thoracentesis, and the type of tumor plays a significant role in the cytological diagnosis.